REAL TIME RENDERING VISUAL EFFECTS IN FILM: VISUAL EFFECTS PRODUCTION WITH UNITY GAME ENGINE - SAYILGAN, YÜCE (ISTANBUL KULTUR UNIV, 2017)
Capacity of digital game engines increased with evolution of microprocessors and many game engines became available by their own developers as a production tool presented for a particular commision or free. In this circumstance, using fields of game engines is expanded and a big developers community has been occured. In this research, I tried to answer the question how we use Unity as one of the next generation game engines for creating visual effects in film development process from a design centric approach. For that purpose, camera shots and real time rendered images composed with chroma key technique.
Keywords: Visual Effect; Game Engine; Chroma Key